2014
DOI: 10.1126/scitranslmed.3009131
|View full text |Cite
|
Sign up to set email alerts
|

Defective PTEN regulation contributes to B cell hyperresponsiveness in systemic lupus erythematosus

Abstract: PTEN regulates normal signaling through the B cell receptor (BCR). In systemic lupus erythematosus (SLE), enhanced BCR signaling contributes to increased B cell activity, but the role of PTEN in human SLE has remained unclear. We performed fluorescence-activated cell sorting analysis in B cells from SLE patients and found that all SLE B cell subsets, except for memory B cells, showed decreased expression of PTEN compared with B cells from healthy controls. Moreover, the level of PTEN expression was inversely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 67 publications
8
128
3
Order By: Relevance
“…Pten +/-mice develop splenomegaly and lymphadenopathy, have increased serum IgG and anti-ssDNA antibodies, and develop lung and kidney inflammation (34). Interestingly, PTEN expression is decreased in SLE patient B cells, and this correlates with increased expression of miR-22 and two other miRNAs, miR-7, and miR-21, that also target PTEN (35).…”
Section: Mirna Regulation Of Peripheral Tolerance and Lymphocyte Funcmentioning
confidence: 99%
“…Pten +/-mice develop splenomegaly and lymphadenopathy, have increased serum IgG and anti-ssDNA antibodies, and develop lung and kidney inflammation (34). Interestingly, PTEN expression is decreased in SLE patient B cells, and this correlates with increased expression of miR-22 and two other miRNAs, miR-7, and miR-21, that also target PTEN (35).…”
Section: Mirna Regulation Of Peripheral Tolerance and Lymphocyte Funcmentioning
confidence: 99%
“…mir-1246 inhibits, by interacting with its 3′-UTr, early B cell factor 1 (eBF1), which is necessary for B cell maturation (pro-B cells, mZ B cells and peripheral B cells) and signalling, including the expression of costimulatory molecules such as cd40, cd80 and cd86 (ref. 144 ). in active sle, B cells showed activation of the pi3K/aKT-p53 signalling pathway leading to alleviation of mir-1246 and enhanced eBF-1 expression 143 .…”
mentioning
confidence: 99%
“…There was also diminished expression of the Foxp3 transcription factor, possibly reflecting deficiency of regulatory T cells linked to activation of mTOR. B cells from SLE patients are found to have decreased expression of PTEN that correlates with disease activity (21). Further investigation showed that microRNA (miRs) that downregulate the expression of PTEN miR-7, miR-21, and miR-22 were increased.…”
Section: Discussionmentioning
confidence: 99%